2021
DOI: 10.3389/fcimb.2021.690087
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Interactions Between Arboviruses and Wolbachia in Aedes aegypti

Abstract: Aedes aegypti is inherently susceptible to arboviruses. The geographical expansion of this vector host species has led to the persistence of Dengue, Zika, and Chikungunya human infections. These viruses take advantage of the mosquito’s cell to create an environment conducive for their growth. Arboviral infection triggers transcriptomic and protein dysregulation in Ae. aegypti and in effect, host antiviral mechanisms are compromised. Currently, there are no existing vaccines able to protect human hosts from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…A few studies reported the interference of endosymbiont bacteria Wolbachia with arboviruses by decreasing host cytoskeletal proteins and lipids essential for arboviral infection. Wolbachia was found to increase host immunity, cellular regeneration and causes the expression of microRNAs, which could potentially be involved in virus inhibition [ 70 ]. This implies that Wolbachia has antiviral properties via its pathogen-blocking effect to reduce the competence of mosquitoes for arbovirus transmission [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies reported the interference of endosymbiont bacteria Wolbachia with arboviruses by decreasing host cytoskeletal proteins and lipids essential for arboviral infection. Wolbachia was found to increase host immunity, cellular regeneration and causes the expression of microRNAs, which could potentially be involved in virus inhibition [ 70 ]. This implies that Wolbachia has antiviral properties via its pathogen-blocking effect to reduce the competence of mosquitoes for arbovirus transmission [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia was found to increase host immunity, cellular regeneration and causes the expression of microRNAs, which could potentially be involved in virus inhibition [ 70 ]. This implies that Wolbachia has antiviral properties via its pathogen-blocking effect to reduce the competence of mosquitoes for arbovirus transmission [ 70 , 71 ]. Currently, it is confirmed that mosquitoes can be infected in nature by Wolbachia .…”
Section: Discussionmentioning
confidence: 99%
“…There can be many factors that influence the efficiency of mosquito arbovirus transmissionperhaps none so important as the quantity of virus ingested by mosquitoes, which in turn is determined by the level and duration of viremia in the host [4]. Other modulating factors may include vector factors (e.g., vector competence [6], feeding preferences [7]), environmental factors (e.g., temperature [8,9]), and the co-occurrence of microorganisms within the mosquito [10][11][12] or within the blood of the vertebrate host [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[11,12], and Aedes albopictus [13,14]. Different Wolbachia strains, i.e., w Melpop, w Mel, and w AlbB, from these natural hosts can exert life-shortening effects [6,10] or confer nutritional benefits [7], efficient maternal transmission [8,15], and antiviral protection [9,16,17]. CI that enables the rapid spread of Wolbachia into insect populations coupled with the antiviral effects of Wolbachia against arthropod-borne viruses forms the basis for the mass release of Wolbachia -transinfected Ae.…”
Section: Introductionmentioning
confidence: 99%